RESEARCH OF AIR IONIZATION OF AIR IN PREMISES ON OPERATION OF COMPUTER EQUIPMENT: Array - Panova, O.; Levchenko, L.; Teslytsky, I. (Municipal economy of cities. Series: «Economy science», 2021)
All known studies on the effect of computer equipment on the concentration of air ions of both signs have been used for rooms where desktop computers are operated. The expediency of conducting research using a laptop computer is substantiated. Therefore, the urgent task is to study the dynamics of the air ionic composition of the air from the operation of personal computers and identify ways to maintain this indicator at the regulatory level. It is shown that the switched on computer deionizes air, and mainly on one polarity. It is established that this is a consequence of electrification of polymer surfaces. The cause of electrification is triboelectric phenomena, including the directional movement of dry air from the CPU cooling fan. Additional electrification (and consequently - deionization of air) gives the presence of the user. Confirmation of the cause of deionization is the slow recovery of the concentration of air ions after turning on the computer to a certain neutralization of surface charges. The dependences of the change of air ion concentrations on the distance from the electric field source are established. At its intensity of about 5 kV/m with dimensions of 1.0×1.0 m, the critical distance is 1.2-1.3 m. It is recommended to carry out wet absorption for an unambiguous workplace, which provides insignificant electric fields for 1.5 hours. During the operation of many personal computers, it is advisable to neutralize surface charges with an ultrasonic humidifier-ionizer. It is emphasized that the conducted research has a separate character. This is due to the presence of specific synthetic materials It is advisable to conduct research in standard rooms for the operation of computer equipment to obtain information that can be summarized and used to develop sanitary standards for the operation of computer equipment.